2014
DOI: 10.5194/gh-69-377-2014
|View full text |Cite
|
Sign up to set email alerts
|

Expanding carceral geographies: challenging mass incarceration and creating a "community orientation" towards juvenile delinquency

Abstract: Abstract. Increasingly, governments are adopting alternative strategies to mass incarceration and drawing on the rhetoric of community to create softer and less restrictive sanctions. This paper argues that this transition provides an opportunity for geographers concerned with incarceration to consider a more expansive understanding of the carceral state. To call for a more geographically expansive consideration of incarceration, this paper draws upon a study of one juvenile court that sought to end racialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…He identifies stop and search, and the policing of the young in general, as liable to result in such deprivations and pains. There is some convergence with the observations of other scholars, such as Hannah-Moffat and Lynch (2012: 119), who have called on criminologists to think beyond ‘what counts as punishment’ (see also Zedner, 2016), and with calls for a more ‘geographically expansive understanding of the carceral’ to explain carceral spaces that extend beyond the prison (Brown, 2014).…”
Section: Youth Race and The Necropolitics Of Policingmentioning
confidence: 71%
“…He identifies stop and search, and the policing of the young in general, as liable to result in such deprivations and pains. There is some convergence with the observations of other scholars, such as Hannah-Moffat and Lynch (2012: 119), who have called on criminologists to think beyond ‘what counts as punishment’ (see also Zedner, 2016), and with calls for a more ‘geographically expansive understanding of the carceral’ to explain carceral spaces that extend beyond the prison (Brown, 2014).…”
Section: Youth Race and The Necropolitics Of Policingmentioning
confidence: 71%
“…Critical carceral studies have rightly demonstrated the broad reverberations of a racially disparate system of mass imprisonment throughout the prison and far beyond (Beckett and Western, 2001;Brown, 2014;Clear, 2009;Crenshaw, 2012;Davis, 2003;Gilmore, 2007;Stanley, 2011). Mass imprisonment is complexly intertwined with housing segregation, as scholars such as Rashad Shabazz (2015) demonstrate the logics of confinement are in no way limited to the prison.…”
Section: A Feminist Curiosity For Corrections and Containmentmentioning
confidence: 99%
“…Instead, mass imprisonment is a new manifestation of a broader culture of surveillance, confinement, and Jim Crow in the United States (Alexander, 2010;McKittrick, 2011;Sudbury, 2005). Collectively, this body of work makes clear the porous nature of the prison (Garland, 2002;Sudbury, 2005) and the capitalistic impulses and neoliberalizing logics that drive its ever-growing expansion to a wider swath of the population (Brown, 2014;Martin and Mitchelson, 2009;Schept, 2015). The drive for austerity will transform the prison, but will it eliminate it?…”
Section: A Feminist Curiosity For Corrections and Containmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the prison is a model that influences a variety of "quasicarceral spaces" (Moran, et al, 2017, p. 14). Based on this understanding, geographers have highlighted the diffuse nature of carceral space itself (Gill, 2103;Brown, 2014;Moran, 2015). Indeed, entire neighborhoods can become quasi-carceral when residents are subjected to intense and targeted policing (Davis, 1990;Peck and Theodore, 2008).…”
Section: Managing Homelessness In the Era Of Mass Incarcerationmentioning
confidence: 99%